COVID-19 Outbreak Effects on Job Security and Emotional Functioning Amongst Women Living With Breast Cancer - Chapman, Bethany; Swainston, Jessica; Grunfeld, Elizabeth A.; Derakshan, Nazanin (Frontiers in Psychology, 2020)
The outbreak of Coronavirus disease 2019 (COVID-19) has severely affected negatively impacted global economies and employment. In the UK, it is predicted that approximately eight million jobs have been were furloughed as a result of the outbreak and the associated restriction of movement or shielding measures. This study aimed to investigate the impact of changes in employment status on cognitive and emotional health as well as perceptions of work. Furthermore, it examined the relationships between women’s job security and anxiety, depression and cognitive function. Women living with breast cancer (N = 234) completed online questionnaires to measure their cognitive function, general emotional wellbeing, COVID-19 related emotional vulnerability (COVID-EMV), work ability and COVID-19 related perceptions of work. Our results revealed that threat to job security was predictive of depression and cognitive function in the entire sample such those with higher levels of perceived job security had lower depression and better cognitive function. Further, women who were furloughed or unable to continue work reported higher job insecurity compared to those who had worked throughout the pandemic. Further, high threat to job security was coupled with greater depression and poorer cognitive function. Greater rumination was also associated with worse anxiety and depression as well as poorer cognitive function. Finally, moderation analysis highlighted that women who had a better cognitive functioning were less likely to experience anxiety when their job security was high. Given our findings, we suggest that employers provide women with accessible interventions to enhance cognitive and emotional resilience and thus help protect against the detrimental effects of job insecurity created by the COVID-19 outbreak.